Existence of at Least Three Distinct Weak Solutions for a Class of Nonlinear System of Fractional Differential Equations. (26th July 2020) - Shivanian, Elyas
Abstract: In this article, it is concerned existence of solutions to a class of nonlinear system of fractional differential equations. It is proved the existence of at least three different weak solutions through the critical point theory and the variational method. In this way, it is applied well-known theorem proved by Bonanno and Marano on the construction of the critical set of functionals with a weak compactness condition. Furthermore, the main result is demonstrated by some examples to show its validity and efficiency.